Penelitian Berkelanjutan Dalam Pariwisata Berbasis Alam: Analisis Bibliometrik Dan Visualisasi - romadhona, sukron (Samarinda State Polytechnic, 2023)
Sustainability, and specifically the need to understand the nature and liminature based tourism of growth, has developed into an important policy issue in tourism literature in the last decade. The objective of the present study is to use a bibliometric approach to review the relevant literature. Bibliometric indicators, such as citations, are used to identify the field structure and the VOSviewer software is used to map the main trends in this area. The bibliometric analysis process comprises three phases: (i) Search Criteria and Source Identification, (ii) software and data extraction, and (iii) data analysis and interpretation.The resulnature based tourism show nature based tourism in full growth as a scientific discipline, thanks to the contribution of various authors, institutions, journals, and related topics that confirm the importance of this field of study. Additionally, bibliometric maps lead to an understanding of the intellectual structure of the subject, in which keyword co-occurrence analysis shows six main themes, ranging from ‘Ecosytem Services’ to ‘Sustainable Tourism’. this, combined with maps of co-citation, broadly exhibinature based tourism this structure and development, showing areas of current interest and potential development, thus offering the latest knowledge nature based tourism research worldwide.